Transformasi Pertanian dan Krisis Air di Bali dalam Perspektif Ekologi Politik - Herlina Tarigan (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2016)
EnglishMass tourism development directing all policies to support tourism in Bali causes water crisis and major agricultural base change. This paper aims to analyze of agricultural transformation process and water crisis taking place in Bali as well as its impacts on the socio-economic cultural life of the society and the future of tourism itself. Using the perspective of political ecology with review techniques, the obtained results are (1) tourism-oriented development policy brings a broad impact on the environment and the agricultural sector especially land conversion, labor, economy, and water resource utilization; (2) water crisis creates natural resource conflict among various stakeholders and tends to marginalize agriculture; (3) local subak institutional decay and it is potential to suppress natural resources and indigenous culture of Balinese society. In the long term, there is a potential that Bali loses its distinctive cultural appeal as the world tourism destination. Using political ecology perspective, it is suggested that Bali has to develop eco-tourism, agro-tourism, and culture-tourism as soon as possible.IndonesianPembangunan pariwisata massal yang mengarahkan semua kebijakan untuk mendukung pariwisata di Bali telah menyebabkan terjadinya krisis air dan perubahan basis utama pertanian. Tulisan ini bertujuan menganalisis proses transformasi pertanian dan krisis air yang terjadi di Bali serta dampaknya bagi kehidupan sosial-ekonomi-budaya masyarakat dan masa depan pariwisata itu sendiri. Menggunakan perspektif ekologi politik dengan teknik review diperoleh hasil bahwa (1) politik pembangunan berorientasi pariwisata membawa dampak yang luas terhadap lingkungan dan sektor pertanian khususnya alih fungsi lahan, ketenagakerjaan, perekonomian, hingga pemanfaatan sumber daya air; (2) terjadi krisis air yang menimbulkan konflik sumber daya alam antarberbagai stakeholder dan cenderung memarginalisasi pertanian; (3) terjadi peluruhan kelembagaan lokal subak dan potensial menekan sumber daya alam maupun kultur asli masyarakat Bali. Dalam jangka panjang, Bali potensial kehilangan daya tarik kultural yang khas sebagai destinasi pariwisata dunia. Menggunakan perspektif ekologi politik, disarankan pariwisata Bali lebih mengarah kepada pengembangan ekowisata, agrowisata, dan kulturwisata.